2023
DOI: 10.3390/foods12020380
|View full text |Cite
|
Sign up to set email alerts
|

A New Laboratory Scale Olive Oil Extraction Method with Comparative Characterization of Phenolic and Fatty Acid Composition

Abstract: The establishment of operation protocols for olive oil (OO) extraction at non-industrial scale is crucial for research purposes. Thus, the present study proposes a simple and cost-effective method for OO extraction at the laboratory scale (LS) level. To validate the proposed methodology, industrial OO extraction (IS) was performed in parallel, using the same cultivars ‘Galega vulgar’ (GV), ‘Cobrançosa’ (COB) and ‘Arbequina’ (ARB) collected from the same orchards, within the same period. Obtained results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Note that the composition of fatty acids is mainly affected by geographical conditions (location, climate and latitude), ripening degree, season and production; it also depends on the genotype [67]. Indeed, several studies reported that the most prevalent fatty acid in virgin olive oil is oleic acid, as it accounts for about 68-82% of the total fatty acids [68][69][70]. Specifically, the percentage of oleic acid obtained in this study confirmed the results provided by [71,72].…”
Section: Discussionsupporting
confidence: 87%
“…Note that the composition of fatty acids is mainly affected by geographical conditions (location, climate and latitude), ripening degree, season and production; it also depends on the genotype [67]. Indeed, several studies reported that the most prevalent fatty acid in virgin olive oil is oleic acid, as it accounts for about 68-82% of the total fatty acids [68][69][70]. Specifically, the percentage of oleic acid obtained in this study confirmed the results provided by [71,72].…”
Section: Discussionsupporting
confidence: 87%